LEGAL PROTECTION FOR APARTMENT CONSUMERS RELATING TO THE FACILITIES PROMISED BY DEVELOPERS (CASE STUDY IN BATAM CITY) - Elza Syarief; Lu Sudirman; Yan Pin (Journal of Law and Policy Transformation, 2022)
People tend to stay closely to the centers of their activities and work activities. Various facilities that are desired by people are also the main objectives in choosing representable housing, including apartments that have various amenities. The high demand for apartments in Batam City has caused developers to compete in building apartments. Unfortunatey, they only focus on business, as the results the promised facilities are sometimes not suitable with the information, they offer to consumers. The issue of the lack of clarity regarding the promised facilities raise legal issues pertaining to the protection of consumers. Legal protection for consumers pursuant to the promised facilities creates new problems in the future. Construction agreements relating to the facilities have been violated by the developers, although they state that they will continue to provide compensation in the form of other amenities. Coordinations according to the mandate of the law and the revision of legal protection against consumers is an alternative offered in this research.